2009
DOI: 10.3201/eid1510.091013
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Airborne Transmission during Outbreak of Pandemic (H1N1) 2009 among Tour Group Members, China, June 2009

Abstract: This outbreak was caused by droplet transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 6 publications
1
70
0
1
Order By: Relevance
“…Flights of longer duration, such as intercontinental flights, may pose a greater risk of transmission, particularly given greater potential for patients on longer flights to develop initial symptoms while on-board as has been found in other investigations. 9,11 However, other investigators who attempted contact investigations during the initial phase of the 2009 pandemic concluded that tracing close contacts among flight passengers was not effective, as timely provision of post-exposure prophylaxis could not be achieved in most cases. 37 Investigation of transmission of novel influenza strains aboard aircraft during the initial phases of an epidemic or pandemic may be instructive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flights of longer duration, such as intercontinental flights, may pose a greater risk of transmission, particularly given greater potential for patients on longer flights to develop initial symptoms while on-board as has been found in other investigations. 9,11 However, other investigators who attempted contact investigations during the initial phase of the 2009 pandemic concluded that tracing close contacts among flight passengers was not effective, as timely provision of post-exposure prophylaxis could not be achieved in most cases. 37 Investigation of transmission of novel influenza strains aboard aircraft during the initial phases of an epidemic or pandemic may be instructive.…”
Section: Discussionmentioning
confidence: 99%
“…Though none were tested to confirm pH1N1 infection, these observations replicate published findings of travelers in groups, who are more likely to contribute to pH1N1 transmission than non-epidemiologically linked air travelers. 10,11 Limitations to this investigation included potential misclassification and recall bias regarding symptoms, dates of onset of illness, and aircraft seating location. In-cabin assessments of the association between illness and proximity to the index case were complicated by the lack of assigned seating on flights A1 and A2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study found that pandemic H1N1/09 virus is transmitted less efficiently via respiratory droplets (16). Droplet transmission does appear to be effective in humans, as an outbreak of pandemic H1N1/09 among tourists in China was caused by talking with the index patient at close range (18).…”
Section: Pathogenesismentioning
confidence: 99%
“…The main route for influenza transmission is via large droplets. Transmission of influenza through the air over longer distances is thought not to occur (8,9). Although the postexposure antiviral prophylaxis was not given to any close contacts, no case occurred among the roommates.…”
mentioning
confidence: 99%